2017
DOI: 10.5194/angeo-35-1219-2017
|View full text |Cite
|
Sign up to set email alerts
|

Unusual behavior of quiet-time zonal and vertical plasma drift velocities over Jicamarca during the recent extended solar minimum of 2008

Abstract: Abstract. The influence of the recent deep and prolonged solar minimum on the daytime zonal and vertical plasma drift velocities during quiet time is investigated in this work. Analyzing the data obtained from incoherent scatter radar from Jicamarca (11.95 • S, 76.87 • W) we observe an anomalous behavior of the zonal plasma drift during June 2008 characterized by lower than usual daytime westward drift and its early afternoon reversal to eastward. As a case study the zonal drift observed on 24 June 2008 is mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In general, the ILs duration was higher during solar minimum than during solar maximum period, for both CP and SL. As the ILs are mainly a diurnal phenomenon with a behavioral pattern very similar to that of the E layer (Dos Santos et al, 2019), the longest lifetime in 2009 can be partially attributed to the weakening of the E region dynamo in this period (Santos et al, 2017). On the other hand, over the equatorial station, the duration of the ILs was lower when compared with the low‐latitude region.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the ILs duration was higher during solar minimum than during solar maximum period, for both CP and SL. As the ILs are mainly a diurnal phenomenon with a behavioral pattern very similar to that of the E layer (Dos Santos et al, 2019), the longest lifetime in 2009 can be partially attributed to the weakening of the E region dynamo in this period (Santos et al, 2017). On the other hand, over the equatorial station, the duration of the ILs was lower when compared with the low‐latitude region.…”
Section: Resultsmentioning
confidence: 99%
“…In this modified version some input parameters, such as atmospheric neutral densities and solar EUV flux, were updated and the field line calculation was extended to lower altitudes in order to include the E region (Bravo et al, 2017;Santos et al, 2016;Souza et al, 2010Souza et al, , 2013. Some studies have demonstrated that this model reproduces well the ionosphere of equatorial, low, and middle latitudes during quiet conditions (Balan et al, 1995;Batista et al, 2011;Nogueira et al, 2013;Santos et al, 2017;Souza et al, 2013;Thampi et al, 2011) and at equatorial-low latitudes during geomagnetic storms (Abdu et al, 2013;Bravo et al, 2017;Santos et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al () investigated the effect of lower geomagnetic activity on ionospheric electron content, Chaitanya et al () analyzed E × B drift impacts on the F 2 and F 3 layers, Ji et al () compared TEC from the JASON‐1 satellite to the International Reference Ionosphere model, Perna and Pezzopane () found good correspondence between the Mg II solar proxy and ionosonde data (cf. Perna et al, ), and Santos et al () observed anomalous zonal plasma drift over Jicamarca in 2008.…”
Section: Introductionmentioning
confidence: 93%